Analisis Peluang dan Tantangan Integrasi Data Kesehatan berdasarkan Aspek 5M (Man, Money, Material, Method and Machine): Analysis of Opportunities and Challenges in Health Data Integration Based on the 5M Aspects (Man, Money, Material, Method, and Machine) - Hanifa, Salihati; Rachmatta Putro Mudiono, Demiawan; Erman Wicaksono, Kurniawan (Journal of Public Health Education, 2025)
Introduction: Digital transformation has become a crucial component of health systems globally, including Indonesia, where health data integration is being implemented through the SATUSEHAT platform as part of the national health system transformation agenda. Objectives: This study aims to analyze the opportunities and challenges of health data integration in Kulon Progo based on 5M framework. Method: This qualitative descriptive study, conducted in Kulon Progo (February–March 2025), employed purposive sampling of 10 informants, with data collected through in-depth interviews and observations guided by structured protocols, to explore opportunities and challenges of health data integration based on the 5M framework. Result: The opportunities for implementing health data integration based on the 5M framework lie in budgeting, infrastructure fulfillment, policy, and technology, while the main challenge remains in the human resources aspect. Conclution: Health data integration in Kulon Progo has been gradually implemented, although challenges remain to be addressed, while there are also opportunities to enhance its implementation based on the 5M aspects.